Métodos de control para el chinche patón Leptoglossus zonatus en el cultivo de pitahaya (Hylocereus undatos). - Alvarado Rosero, José Antonio (2020)
The stump bug Leptoglossus zonatus is one of the main pests that affect the pitahaya crop causing damage and losses. There are different methods for the control of this type of pest but before using any method we must highlight the meaning of IPM integrated pest management within this management we find the biological control for the patón bedbug being a preventive and lasting strategy in addition to being Oriented by ecology and human health, there is also chemical control but we must raise awareness that this method is applied as a last resort, because it is harmful to human health and the environment, but it is efficient in the high incidence of this plague. The current study of this case aims to describe the methods of control of the stink bug in the pitahaya crop. For the development of the current document, bibliographic information was collected from books, magazines, scientific articles, web pages, lectures, technical manuals, the information obtained was carried out through analysis and synthesis technique in order for the reader to understand the importance of choosing a good method for the stump bug without harming the crop or the ecosystem Through research we can understand that the management of the different methods helps to increase and develop the production of the pitahaya crop, which will help to obtain better profits and thus improve the quality of its economy.